ANALISIS KESULITAN BELAJAR SISWA DALAM MEMAHAMI MATERI TENTANG KERAPAN SAPI PADA PEMBELAJARAN BAHASA INDONESIA DI SDN PROPPO 1 - Cahya Wilda Syahningrum Harlambang; M. Fadlillah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
As times change, many students today are less familiar with the local wisdom of their respective cultures. Therefore, it is crucial in the world of education to support students' ability to understand their local wisdom by connecting it to what they learn in school. This is especially important for instilling an understanding of their region's local wisdom from a young age. Students' ability to understand learning concepts varies from one student to another. Factors contributing to learning difficulties include two types: internal factors such as motivation and lack of interest in learning, and external factors such as teaching methods and environment, which can hinder students from achieving maximum results. This study aims to analyze students' learning difficulties in understanding the material about cattle density in Indonesian language learning for fourth-grade students at SDN Proppo 1. This research uses data collection techniques including interviews, observation, and documentation. The subjects in this study are the fourth-grade homeroom teachers. The research outputs include a proposal, progress and final reports for MBKM, a logbook, a poster, and a draft scientific article.